Digital Video Editing Fundamentals - Jackson, Wallace (Apress : Imprint: Apress, 2016)
This compact visual guide covers concepts central to digital video using the affordable Corel Video Studio Ultimate X9 software package as well as open source digital video editing package Editshare Lightworks 12. Inside, you'll learn the following: · What is the terminology of digital video editing and special effects · What comprises a digital video editing and effects pipeline · What are the concepts behind digital video terminology · How to install and use Corel Video Studio Ultimate X8 · What are the concepts behind Resolution, Aspect Ratio, Bit Rate and Color Depth · How to use digital video file formats and data footprint optimization.